Towards a better understanding of shallow erosion resistance of subalpine grasslands. (15th December 2020) - Löbmann, Michael Tobias; Tonin, Rita; Stegemann, Jan; Zerbe, Stefan; Geitner, Clemens; Mayr, Andreas; Wellstein, Camilla
Abstract: Shallow erosion is caused by processes such as landsliding, snow gliding, avalanches, animal trampling, or human activities and frequently occurs on high mountain grasslands. It can lead to significant long-term losses of grassland and related ecosystem services, e.g. fodder production, or water retention. Since restoration of subalpine and alpine ecosystems is difficult, prevention of shallow erosion is of vital importance for damage control. However, current knowledge on relationships between grassland ecology, management and shallow erosion resistance is very limited. In this study, we assessed relationships between the surface-mat stability of the topsoil (0–10 cm depth), vegetation cover, species diversity, growth patterns, indicator plant species for high and low tensile strength, soil texture, total nitrogen, and soil organic carbon. Vegetation composition significantly influenced the surface-mat stability of subalpine grasslands. Some key species were associated with higher reinforcement than other species. However, surface-mat stability neither depended on the vegetation type (grass or forb), nor on the root type, but rather on individual species characteristics such as roots and clonal structures as well as a certain plant and structural diversity. A balanced nutrient supply was associated with higher surface-mat stability, while soil texture had no effect. We hypothesized that stabilizing effects of plant-plant connections in tightly interwoven, dense root and clonal structure systems dominate over effects of root-soil connections. Thus, effects of soil texture may be negligible for the surface-mat stability. In general, our results show that adapted grassland management can be used as preventive erosion control measure on subalpine grasslands. Graphical abstract: Image 1 Highlights: Vegetation composition affects the topsoil tensile strength (surface-mat effect). Influence on the surface-mat effect is species-specific. Clonal structures (e.g. rhizomes) play an important role for slope stability. Intermediate nitrogen availability improves the surface-mat effect, soil texture has no effect. Adapted grassland management can be used as preventive erosion control measure.